89.8k views
3 votes
F(x) = -4(x+3)+6(x+4)

User TommyN
by
4.7k points

1 Answer

1 vote

Answer:

zero of the function occurs at x = -6

Explanation:

Given f(x) = -4(x+3)+6(x+4)

Since the question is incomplete, we can as well find the zero of the given function. The zero exists when f(x) = 0

Hence;

-4(x+3)+6(x+4) = 0

Expand

-4x - 12 + 6x + 24 = 0

Collect the like terms

-4x + 6x - 12 +24 = 0

2x + 12 = 0

2x = -12

x = -12/2

x = -6

Hence the zero of the function occurs at x = -6

User Aebmad
by
5.1k points